Antibacterial Activity of Kayu Ulin Bark Ethanol Extract Against Acne-Causing Bacteria - Novaryatiin, Susi; Hidayat, Muhammad Aripin; Ardhany, Syahrida Dian (LPPM Universitas Bakti Tunas Husada, 2024)
There are several social, cultural, and economic benefits to cultivating the native Kayu Ulin (Eusideroxylon zwageri Teijsm. & Binn.) in Kalimantan. The Dayak tribe utilizes the Kayu Ulin for herbal medicinal purposes, with its skin and roots proving effective in treating skin conditions such as acne, boils, and wound infections. Staphylococcus aureus, Staphylococcus epidermidis, and Cutibacterium acnes are the root cause of acne, a skin infection. This study aimed to find out the potential of the ethanolic extract of Kayu Ulin bark as an antibacterial agent for acne bacteria. This study used the disc-diffusion (Kirby-Bauer) technique for extraction, which involved the soxhletation process with 96% ethanol as the solvent. Each of the four concentrations of the extract—1%, 5%, 10%, and 15%—was tested three times to determine its antibacterial activity. The study's results showed that the ethanolic Kayu Ulin bark extract is effective in suppressing the growth of S. aureus, S. epidermidis, and C. acnes. Moderate inhibition of C. acnes was seen at concentrations of 1%,5%, and 15%. However, most extract concentrations tested on S. epidermidis showed weak activity. The highest inhibition zone was observed with the 15% ethanol extract of Kayu Ulin bark against S. aureus, measuring 9.8±4.3 mm, categorizing it as a moderate inhibitory response. Further research is warranted to explore the inhibitory capabilities using different extraction methods.